Gamification of chemistry with Stoichio-TRI riddle card game - Raja Anuar, Raja Anis Husna; Mohd Rosle, Nur Awatif Afiqah; Faisal, Akhtar; Md Nor, Nurur Raudzah; Mohd Ali, Noor Saadiah (ASIAN SCHOLARS NETWORK, 2025)
The complexity of chemistry serves as motivation to create innovative teaching and learning pedagogical approaches. This pedagogy includes the application of game mechanisms in the subject matter to enhance the processes enacted and to make education more interactive and engaging. It also fosters a positive learning environment, especially for the physical chemistry subject that involves various chemical reactions, formulas, calculations, and principles. The aim of this project is to evaluate the effectiveness of educational gamification as a medium for learning chemistry. It is focused on increasing the students’ understanding and mastery of the chemical reactions and stoichiometry topic. The innovation known as the “Stoichio-TRI riddle” card game was designed based on a puzzle riddle embedded with the curriculum content from the selected topic. The game could promote the skill of critical Thinking, active Recall, and Interaction among students (TRI). The test population consisted of the current students at the International Islamic University Malaysia (IIUM) taking the Sciences foundation program. Data were gathered from students’ pre-test, post-test of the stoichiometry topic, and evaluation form through online questionnaires. The result indicated that the “Stoichio-TRI riddle” card game is helpful in enhancing students’ understanding of stoichiometry reactions in chemistry and contributes insights into optimizing educational strategies by emphasizing the role of active recall in fostering robust and enduring knowledge acquisition compared to the traditional lecture-based teaching model. Indeed, this innovation offers a promising approach to engage students in a more interactive and enjoyable experience.